The effect of capital structure, financial distress and company size on tax avoidance - Wijaya, Dimas Aris; Romadhina, Anggun Putri (Educoretax, 2025)
This study aims to analyze the effect of capital structure, financial distress, and company size on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The data used in this study are financial reports that include important information about the companies' financial performance. The sampling technique used is purposive sampling, where from 87 energy sector companies, 16 companies were obtained over 5 years, resulting in a total of 80 samples analyzed. The analysis used in this study is panel data regression analysis, which allows researchers to evaluate data with both time and individual dimensions simultaneously. The data was processed using Eviews 12 and Microsoft Excel 2019 software, which facilitated data processing and analysis. The results obtained indicate that capital structure, financial distress, and company size simultaneously have a significant effect on tax avoidance. However, the partial analysis results show that capital structure does not affect tax avoidance, financial distress does not affect tax avoidance, and company size does not affect tax avoidance. These findings indicate that the proportion of debt in the financing structure, financial distress, and company size do not directly influence companies' decisions to engage in tax avoidance. This study provides important insights for stakeholders and regulators to understand the factors influencing tax avoidance in the energy sector. Additionally, the results of this study can serve as a basis for developing more effective policies to enhance tax compliance in this industry, as well as promoting greater transparency and accountability.